1993
DOI: 10.1029/92jb01889
|View full text |Cite
|
Sign up to set email alerts
|

Thermobarometric constraints on the depth of exposure and conditions of plutonism and metamorphism at deep levels of the Sierra Nevada Batholith, Tehachapi Mountains, California

Abstract: We present thermodynamic estimates of pressures, temperatures, and volatile activities in vailably deformed, gabbroic to granitic, Cretaceous (115-100 Ma) batholithic and framework rocks of the Tehachapi Mountains, southernmost Sierra Nevada, California. A1 contents of hornblende in granitoids imply igneous emplacement at --8 kbar in the southernmost Tehachapi Mountains, with lower pressures (3-7 kbar) to the north. Metamorphic pressures and temperatures for garnet-bearing paragneisses and metaigneous rocks we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 49 publications
4
109
0
Order By: Relevance
“…The assumptions of localized tectonic extension and repeated diking events likely contribute to heat preservation and construction of mush regions. There are relatively limited geophysical constraints on the expanse and residence time for lower crustal melt that focus on: 1) petrologic observations on exhumed lower crustal terrains that include for example Ivrea, North Italy (e.g., Sinigoi et al, 1994;Voshage et al, 1990;Wedepohl, 1995); Kohistan, Pakistan (e.g., Burg, 2011;Dhuime et al, 2009;Jagoutz et al, 2007;Jagoutz and Schmidt, 2012); Fraser and Musgrave Ranges, Australia (e.g., Fletcher et al, 1991;White et al, 1999); Sierra Nevada and Peninsular Ranges, California (e.g., DePaolo, 1981a;Pickett and Saleeby, 1993); Fiordland, New Zealand (e.g., Klepeis et al, 2003) and 2) seismic studies exemplified by Main Ethiopian Rift (e.g., Keranen et al, 2004) and Western United States (e.g., McCarthy and Thompson, 1988). However, while useful, these observations provide a limited picture of the temporal history of lower crustal magmas.…”
Section: How Do Extensional Processes Affect Melt Location and Residementioning
confidence: 99%
“…The assumptions of localized tectonic extension and repeated diking events likely contribute to heat preservation and construction of mush regions. There are relatively limited geophysical constraints on the expanse and residence time for lower crustal melt that focus on: 1) petrologic observations on exhumed lower crustal terrains that include for example Ivrea, North Italy (e.g., Sinigoi et al, 1994;Voshage et al, 1990;Wedepohl, 1995); Kohistan, Pakistan (e.g., Burg, 2011;Dhuime et al, 2009;Jagoutz et al, 2007;Jagoutz and Schmidt, 2012); Fraser and Musgrave Ranges, Australia (e.g., Fletcher et al, 1991;White et al, 1999); Sierra Nevada and Peninsular Ranges, California (e.g., DePaolo, 1981a;Pickett and Saleeby, 1993); Fiordland, New Zealand (e.g., Klepeis et al, 2003) and 2) seismic studies exemplified by Main Ethiopian Rift (e.g., Keranen et al, 2004) and Western United States (e.g., McCarthy and Thompson, 1988). However, while useful, these observations provide a limited picture of the temporal history of lower crustal magmas.…”
Section: How Do Extensional Processes Affect Melt Location and Residementioning
confidence: 99%
“…The bounding structure is the Rand fault, a structurally modified subduction megathrust flat that the schist protolith assemblage was originally subducted along. Metamorphic equilibration pressures in the Rand schist are $9 kb [Pickett and Saleeby, 1993;Jacobson, 1995]. Equilibration pressures in proximal upper plate rocks range from 7 to 11 kb.…”
Section: Geologic Settingmentioning
confidence: 99%
“…Exhumation of the batholith commonly has been assumed to have occurred by erosion, with much of the removed material deposited immediately to the west of the batholith as forearc basin sediments that today are exposed along the western side of the San Joaquin and Sacramento valleys (Mansfield, 1979;Bateman, 1992). The southernmost part of the batholith south of Lake Isabella, in contrast, has been exhumed to much deeper crustal lev els of ~15 to 30 km (Sharry, 1981;Ague and Brimhall, 1988;Pickett and Saleeby, 1993), which means that more of the batholithic crust in the south has been removed and transported elsewhere. Malin et al (1995) suggested that crustal thickening related to emplacement of Rand Schist beneath the southernmost Sierra Nevada batholith in Late Cretaceous time may have led to the subsequent collapse of the crust and exhumation of the deep-level rocks in the region along normal faults.…”
mentioning
confidence: 94%